2011
DOI: 10.1093/bja/aer041
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil patient-controlled analgesia effect-site target-controlled infusion compared with morphine patient-controlled analgesia for treatment of acute pain after uterine artery embolization

Abstract: Remifentanil PCA-TCI with a slow and progressive adapted algorithm without any associated premedication or co-medication is feasible in young healthy women undergoing UAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The natural history of PI associated with UAE is that it remains severe during and for several hours after UAE and then decreases in intensity [4]. This has been reflected in other studies [15] that have measured the pattern of opioid use in the 24 h after UAE, and also in our study where mean PCA opioid across both groups was much less in the 6 to 24 h period (6.28 mg) compared to the 0 to 6 h period (14.9 mg). We also provided an oral dose of oxycodone which should have provided a peak concentration at approximately 3.2 h [21,22], theoretically matching the time period of peak analgesic requirement.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The natural history of PI associated with UAE is that it remains severe during and for several hours after UAE and then decreases in intensity [4]. This has been reflected in other studies [15] that have measured the pattern of opioid use in the 24 h after UAE, and also in our study where mean PCA opioid across both groups was much less in the 6 to 24 h period (6.28 mg) compared to the 0 to 6 h period (14.9 mg). We also provided an oral dose of oxycodone which should have provided a peak concentration at approximately 3.2 h [21,22], theoretically matching the time period of peak analgesic requirement.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies [14][15][16] showed that morphine PCA provided superior PI ratings after UAE in a nonrandomized setting compared with fentanyl PCA [16]. In the remaining randomized controlled studies, morphine PCA was associated with greater early PI compared with target-controlled remifentanil [15] and when compared with morphine PCA combined with localized intra-arterial lidocaine injection [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA without background infusion is also used. Post-operative PCA usage has been described for analgesics such as morphine, piritramide, fantanyl, tramadol, and others [47][48][49][50][51]. In a systematic review, Walder and colleagues showed that the some evidence exists that in the postoperative pain setting, PCA with opioids, compared with conventional opioid treatment, improves analgesia and decreases the risk of pulmonary complications, and that patients prefer this option [52].…”
Section: Examples Of Closed-loop Drug Administrationmentioning
confidence: 99%
“…At the time this study was initiated, the standard of care to treat pain following UFE included the administration of oral or intravenous (IV) opioids and non-steroidal anti-inflammatory drugs (NSAID). Several options for post-procedural pain control have been suggested, many of which use opioid-based IV patient-controlled analgesia (PCA) with oral NSAIDs [9,10]. However, opioid-based therapy may result in dose-dependent side effects such as nausea, drowsiness, itching, sedation and respiratory depression [11].…”
Section: Introductionmentioning
confidence: 99%